1995
DOI: 10.1016/0020-7292(94)02237-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern of the Indian fetus

Abstract: Slowing of growth of the fetal AC after 28 weeks and a shorter length of gestation result in the birth of smaller babies in this ethnic group. The implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…Nonetheless, technique may influence the results if our ultrasonographers systematically measured longer femur length than the reference. Femur lengths similar to reference populations were reported in other populations with low average birth lengths (39,40). This apparent inconsistency could be explained by shorter trunk length in infants who were stunted at birth.…”
Section: Tablementioning
confidence: 61%
“…Nonetheless, technique may influence the results if our ultrasonographers systematically measured longer femur length than the reference. Femur lengths similar to reference populations were reported in other populations with low average birth lengths (39,40). This apparent inconsistency could be explained by shorter trunk length in infants who were stunted at birth.…”
Section: Tablementioning
confidence: 61%
“…In the present study fundal height measurement showed more positive diagnostic value than abdominal girth, this finding is in accordance with the findings of Mathai and Indira. 33,34 USG is a very important investigation in diagnosis and monitoring of IUGR. BPD was found to lag behind in IUGR group than that of control group from 28 weeks onwards in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 370: 20140067 relative to European women [76][77][78][79]. This might indicate a modest fetal co-adaptation to smaller birth canal in hot-adapted populations, but although acute heat stress has been linked with preterm delivery [80], robust support for a link between mean gestation duration and climate remains lacking.…”
Section: Why Cannot the Offspring Be Smaller?mentioning
confidence: 99%